Revitalisasi Sastra Berbasis Kearifan Lokal Melalui Pelatihan Usaha Tas Jinjing Kata Untuk Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia Tahun 2023 - Patrisia Cuesdeyeni; Albertus Purwaka; Misnawati Misnawati; Syarah Veniaty; Yulina Mingvianita; Wihadi Admojo (FKIP, Universitas Palangka Raya, 2023)
One of the goals of entrepreneurship education at the tertiary level is to mold students into someone who is good at finding business opportunities according to the field they are in. As well as making this opportunity a new job field. However, the problem faced by students of the Indonesian Language and Literature Education Study Program, FKIP, UPR is the lack of skills and creative ideas related to self-development towards independent entrepreneurship. Learning in the Entrepreneurship course is limited to theory and developing theory into a design or design of entrepreneurial activities in the form of a proposal. Therefore, real practice is needed which involves students directly in related entrepreneurship (management and production processes) of a business. The purpose of this service activity is; 1) to increase the interest of students of the Indonesian Language and Literature Education Study Program in entrepreneurship, 2) to increase the understanding of students of the Indonesian Language and Literature Education Study Program regarding the management of the Tas Jinjing Kata business, and 3) to maintain literature based on Central Kalimantan local wisdom by students Indonesian Language and Literature Education Study Program in entrepreneurship.The method used in this community service activity is a process method which includes three stages, namely; 1) preparation, 2) implementation and 3) evaluation. The results of this community service activity are: 1) Implementation of entrepreneurship socialization activities for students of the Indonesian Language and Literature Education Study Program, 2) implementation of training and mentoring activities for the Word Tote Bag business through structured stages, 3) Tas Jinjing Kata products, and 4) media accounts social media as a means of product publication. Based on the results of the activity, it can be concluded that entrepreneurship training and mentoring activities are able to develop students' creative ideas and provide basic knowledge about the management of a business product